Balkanistic Perspectives from a Roundtable in Sofia - Lyudmila Mindova (Zeszyty Cyrylo-Metodiańskie)
A report on the Roundtable in honor of Dr. Sanya Velkova-Kozhuharova: ‘History and Culture of the Balkans: Foreign Influences, Contextual Adaptation, Hybrid Phenomena’ (Sofia, Institute of Balkan Studies and Centre of Thracology of the Bulgarian Academy of Sciences, 2–3 November 2023). Original title in Bulgarian: Балканистични перспективи от кръгла маса в София.